Work-Family Human Resource Bundles And Perceived Organizational Performance - Perry-Smith, Jill; Blum, Terry C. (Academy of Management Journal, 2000)
Although typically excluded from strategic human resource models, bundles of work-family policies may be an HR approach related to competitive advantage. Symbolic action and resource-based views provide conceptual support for such a relationship. Results from a national sample of 527 U.S. firms suggest that organizations with more extensive work-family policies have higher perceived firm-level performance. In addition, there was partial support for the hypotheses that the relationship between work-family bundles and firm performance is stronger for older firms and firms employing larger proportions of women.